2018
DOI: 10.1016/j.virol.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Localization to detergent-resistant membranes and HIV-1 core entry inhibition correlate with HIV-1 restriction by SERINC5

Abstract: SERINC5(S5) is a multi-span transmembrane protein that potently blocks the infectivity of HIV-1 produced by human T-cells. The ability of S5 to restrict infectivity correlates with its presence in the virion, but the exact mechanism by which S5 restricts HIV-1 is unknown. Here we tested whether the core from HIV-1 virions containing S5 is delivered to the cytoplasm. Using the "fate of the capsid" assay, we demonstrated that the viral core of S5-restricted HIV-1 does not reach the cytoplasm of target cells, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 27 publications
7
78
1
Order By: Relevance
“…We produced fluorescent NL4-3 and THRO virions in 293T or 293T cells stably expressing CD4 (293T-CD4), with or without transient transfection of SERINC5. To limit possible artifacts due to excessive expression of SERINC5 in producer cells, we used 20-fold less SERINC5 plasmid than proviral DNA (57). We tested the infectivity of viral particles and stained producer cells and ultracentrifuged viral particles as described above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We produced fluorescent NL4-3 and THRO virions in 293T or 293T cells stably expressing CD4 (293T-CD4), with or without transient transfection of SERINC5. To limit possible artifacts due to excessive expression of SERINC5 in producer cells, we used 20-fold less SERINC5 plasmid than proviral DNA (57). We tested the infectivity of viral particles and stained producer cells and ultracentrifuged viral particles as described above.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it will be interesting to investigate directly how SERINC5 affects the exposure of other Env domains, such as the Gp41/Gp120 interface or MPER. Previous studies suggested that SERINC5 significantly increases the neutralization sensitivity to these anti-Env antibod-ies (41,57,67). Also, including Nef mutants unable to counteract SERINC5 (68) will help dissecting the complex interplay between Nef, Env, and SERINC5 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be required to test the functional significance of phosphatidylserine, sulfatide and/or cholesterol binding in biological functions of SERINC proteins. Affinity for cholesterol and/or exposed phosphatidylserine could help explain the association of SERINC5 with lipid rafts 9,26 and ultimately incorporation of the protein into budding virions.…”
Section: Discussionmentioning
confidence: 99%
“…To identify regions of SERINC5 involved in HIV-1 restriction, we conducted an extensive mutagenesis screen, informed by the structure and amino acid sequence conservation with SERINC2, which lacks the HIV-1 restriction activity 9,10 . The mutations were introduced into constructs designed to express SERINC5 harbouring a FLAG epitope implanted within ECL4.…”
Section: Mapping Serinc5 Regions Critical For the Antiviral Activitymentioning
confidence: 99%
“…SERINC5 seems to be the most potent restrictor and accounts for the majority of the Nef effect (at least in T cell lines); in contrast, SERINC3 has modest restrictive activity, and SERINC2 is devoid of restrictive activity (16,17). The study of chimeras between the nonrestrictive SERINC2 and the restrictive SERINC5 led to a partial mapping of SERINC5's restrictive activity (20). While the ability of SERINC5 to restrict HIV-1 infectivity is conserved among vertebrates, sensitivity to Nef is not.…”
mentioning
confidence: 99%